P10 Long term health effects of NEET experiences: evidence from scotland. (September 2018) - Feng, Z; Ralston, K; Everington, D; Dibben, C
Abstract : Background: Reducing the number of young people not in employment, education or training (NEET) is high in political agenda in many countries. The Europe 2020 flagship initiative Youth on the Move introduce a number of programmes that tackle this problem. Although NEET young people have been identified as one of the most vulnerable groups since the 1990s, little is known about the long-term effect of NEET experiences, especially the health consequences. This paper investigates whether experiences of NEET young people are associated with poor health. Methods: We used the Scottish Longitudinal Study (SLS), which collates information from the 1991, 2001, and 2011 censuses as well as from vital events, for a 5.3% representative sample of the Scottish population. Linked health data such as hospital admissions and prescribing in general practice are also available. We followed around 14 000 young people who were aged 16–19 in 1991 up to 2010. We explored whether NEET young people in 1991 displayed higher risks of poor physical and mental health in the follow-up period. Three health outcomes are used in the analysis: mortality, hospitalisation and prescription of anti-depressant and anti-anxiety medication. We used logistic regression to model the probability of hospitalisation and poor mental health. We fitted a Cox proportional hazards model to model time to death. Covariates include a number of individual socioeconomic characteristics and local area characteristics. Results: Over 40% of the cohort members have been admitted into hospital, while over 15% have been prescribed with anti-depressant and anti-anxiety drugs, and 1% died in the follow-up period. The NEET status in 1991 appears to be associated with hospitalisation with adjusted odds ratio (OR) of 1.24 (95% Confidence Intervals (CIs): 1.08–1.42). Also the NEET experiences are associated with poor mental health with OR of 1.47 (95% CI 1.27 to 1.71). The hazard ratio of death for NEETs is more than twice that for non-NEETs (HR: 2.5 95% CI 2.2 to 2.9). The elevated risk remained even when the models were fitted separately by gender. Conclusion: We found that NEET experiences are associated with elevated risks of mortality, hospitalisation and poor mental health. Disengagement from employment and education during transition from school to work may lead to long term negative health effects which in turn results in social and economic costs to society. Policy intervention is necessary in assisting NEET young people to re-engage in education or employment.